Increasing Student Reading Interest in the availability of Collections at the Nahdlatul Ulama Sunan Giri University Library - Abdul Basith; Ainu Zuhriyah (al-Afkar, Journal For Islamic Studies, 2024)
Libraries are a very important place for the community, especially for students to access various types of books and other sources of information. The library not only provides a collection of books, but also a place to study, research, and develop knowledge. In addition, libraries are often the center of cultural and educational activities in their communities. The aim of the research is to increase students' interest in reading regarding the availability of collections in the library of Nahdlatul Ulama Sunan Giri University. Quantitative descriptive research method by conducting observations, interviews and documentation. The results obtained from the homes of 105 students sampling 50 students, amounting to 73.8% of respondents or visitors, said that reference books according to courses were already available in the library.  Interest in learning according to students. These results can be proven by 55.6%, saying Yes. 50.6% of student library materials were obtained. The conclusion of the relationship between the learning interests of Nahdaltul Ulama Sunan Giri University students and the availability of library collections is proven by a correlation coefficient of 5%, meaning that there is a very close relationship between the two.